Improving Students’ Oral Performance through Classroom Interactive Debates The Case of Second Year LMD Students of English at Mohamed Boudiaf University of M‟Sila - BENDAKFEL Selma, GUEMRAOUI Linda (My University, 2020)
Although speaking reflects how well a speaker masters the target language, many foreign language students at advanced levels have different difficulties in speaking. Hence, this research investigates teachers and students' attitudes towards the effectiveness of classroom debate in enhancing students' oral performance. The hypothesis raised in this study sets out that teachers and students have positive attitudes towards the effectiveness of classroom debate in improving students' oral performance and using debate techniques develops students‟ oral performance in terms of accuracy, fluency, pronouncing and vocabulary. The research method adopted for this study was descriptive since the data is gathered through two main questionnaires. Therefore, fifty questionnaires were administered to second year LMD students, and only 25 were analyzed and discussed besides forty questionnaires for English teachers. The results obtained have shown that classroom debate is an effective pedagogical tool for enhancing students' oral performance. Classroom debate motivates students to express themselves, use language orally in a given context, and think critically when discussing their ideas. Based on these results, the previous stated hypothesis was confirmed and some recommendations are put forward. Teachers should encourage students centered classes through classroom debate. Students ought to overcome their difficulties through engaging in debate activities in order to develop their oral performance.
Keywords: Keywords: Debate, Speaking, Effectiveness